STUDI KASUS PELAKSANAAN PROGRAM TOILET TRAINING ANAK MULTIPLE DISABILITY WITH VISUAL IMPAIRMENT (MDVI) DI SLB-A YPAB SURABAYA - EKO SUSENO, YUDHA; , MURTADLO (Jurnal Pendidikan Khusus, 2018)
ABSTRACT THE STUDY CASE OF THE IMPLEMENTATION OF TOILET TRAINING PROGRAM TO MULTIPLE DISABILITIES WITH VISUAL IMPAIRMENT (MDVI) CHILDREN Name : Yudha Eko Suseno NIM : 14010044059 Study Program : S-1 Department : Special Education Faculty : Education Science Institution : Surabaya State University Counselor : Prof. Dr. H. Murtadlo, M.Pd The disability condition experienced by multiple disabilities with visual impairment children had impact to the obstructed of the children?s toilet training abilities; therefore, it required teaching toilet training to help the problem above. This research had purpose to describe about the ability and the implementation of toilet training program to multiple disability with visual impairment (MDVI) children in SLB YPAB Surabaya. This research used qualitative research method with study case approach. One MDVI child involved as the subject observed. The technique of data collection used the technique of interview, observation, and performance test. The inspection of data validity used source triangulation, technique triangulation, and time triangulation. The research result indicated that the implementation of teaching toilet training used oral technique and modeling / prompting technique. The success of toilet training to MDVI children was influenced by several factors such as, physical readiness, psychological readiness, and intellectual readiness. Beside that the consistent attitude in teaching toilet training and supporting available facility also had role in the success of toilet training to MDVI children. Keywords: Toilet training, multiple disability with visual impairment (MDVI) children ABSTRAK STUDI KASUS PELAKSANAAN PROGRAM TOILET TRAINING ANAK MULTIPLE DISABILITY WITH VISUAL IMPAIRMENT (MDVI) DI SLB-A YPAB SURABAYA Nama : YudhaEkoSuseno NIM : 14010044059 Program Studi : S-1 Jurusan : Pendidikan Luar Biasa Fakultas : Fakultas Ilmu Pendidikan Nama Lembaga : Universitas Negeri Surabaya Pembimbing : Prof.Dr.H. Murtadlo, M.Pd Kondisi ketunaan yang dialami anak multiple disability with visual impairment berdampak pada terhambatnya kemampuan toilet training anak, maka dari itu diperlukan adanya pengajaran toilet training untuk membantu masalah tersebut. Penelitian ini bertujuan untuk mendeskripsikan tentang kemampuan dan pelaksanaan program toilet training anak multiple disability with visual impairment (MDVI) di SLB-A YPAB Surabaya. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Melibatkan satu orang anak MDVI sebagai subjek yang diteliti. Teknik pengumpulan data menggunakan teknik wawancara, observasi dan tes performance. Pemeriksaan keabsahan data menggunakan triangulasi sumber, triangulasi teknik dan triangulasi waktu. Hasil penelitian menunjukkan bahwa pelaksanaan pengajaran toilet training menggunakan teknik lisan dan teknik modelling/prompting. Keberhasilan toilet training anak MDVI dipengaruhi oleh beberapa faktor seperti kesiapan fisik, kesiapan psikologis, kesiapan intelektual. Selain itu sikap konsisten dalam mengajarkan toilet training dan tersedianya fasilitas pendukung juga berperan dalam keberhasilan toilet training anak MDVI. Kata kunci: toilet training, MDVI